(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article examines the correlation, in the poetry of the elder English Romantic poets, between the images of the Golden Age, the restored Paradise, and the New Jerusalem, as well as the gradual transformation of these images. It also considers Byron’s interpretation of humankind and human history through the biblical myth in comparison with the interpretations of his elder contemporaries. It is argued that the key poles of the polemic on Paradise in English Romantic poetry are the discourse of the lost and the new Paradise, formed in the works of the elder Romantics, and its transformation in Byron’s works, which rests on the rejection of the possibility of both universal and individual Paradise.